2015
DOI: 10.1111/mec.13354
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection underlies the species‐specific binding of Plasmodium falciparum RH5 to human basigin

Abstract: Plasmodium falciparum, the causative agent of the deadliest form of malaria, is a member of the Laverania subgenus, which includes ape-infecting parasites. P. falciparum is thought to have originated in gorillas, although infection is now restricted to humans. Laverania parasites display remarkable host-specificity, which is partially mediated by the interaction between parasite ligands and host receptors. We analyse the evolution of BSG (basigin) and GYPA (glycophorin A) in primates/hominins, as well as of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 52 publications
(172 reference statements)
0
34
0
Order By: Relevance
“…A subsequent population genetic/phylogenetic analysis conducted by Forni et al . [33] found that several of these residues have undergone positive selection in great apes, while a Pf Rh5 residue that stabilizes the interaction with BSG has also been positively selected.…”
Section: Plasmodium Falciparum and The Laverania: A Highly Host Restrmentioning
confidence: 99%
“…A subsequent population genetic/phylogenetic analysis conducted by Forni et al . [33] found that several of these residues have undergone positive selection in great apes, while a Pf Rh5 residue that stabilizes the interaction with BSG has also been positively selected.…”
Section: Plasmodium Falciparum and The Laverania: A Highly Host Restrmentioning
confidence: 99%
“…Specific amino acid residues in BSG were identified that contribute to recognition of human BSG by PfRh5. Notably, two of these residues, F27 and K191, were identified as targets of positive selection in a study using population genetics and phylogenetics (Forni et al 2015), providing further evidence that this key receptor is under selection pressure both within the human lineage and during NHP evolution.…”
Section: Pfrh5 As a Host Restriction Factormentioning
confidence: 88%
“…vivax / P . knowlesi (Duffy antigen) were previously shown to have evolved under positive selection in primate phylogenies 66 , 67 . It is thus conceivable that other genes that encode molecules involved in Plasmodium infection or pathogenesis have evolved to avoid or limit the fitness costs imposed on primates by these parasites.…”
Section: Discussionmentioning
confidence: 99%